Nilai-Nilai Kearifan Lokal Daerah Lampung dalam Materi Pembelajaran Bahasa Indonesia dan Relevansinya Terhadap Pendidikan Karakter - Izhar; Fitriati, Siti; Astuti, Rr. Dwi (Universitas Muhammadiyah Kotabumi, 2024)
In the current era of globalization, character education is encouraged in learning activities, including learning Indonesian. It was not without cause. Lack of respect, lack of mutual assistance, language impoliteness, and other negative attitudes are problems and the root of suppressing the character of education in educational institutions. It means that language learning is not only about being able to communicate verbally or in writing; language learning also needs to question the character of the language user, namely the language learner himself, as the target. For this reason, it is essential for language teaching to instil character values ​​in language learning materials. This research aims to describe the local wisdom values ​​of the Lampung region and try to insert them into Indonesian language learning materials, especially regarding expository text material for class XI high school students. This qualitative research describes the local wisdom values ​​of the Lampung region and tries to insert these values ​​into Indonesian language learning. Data collection techniques were carried out using literature studies and interviews. The results of the research study show that the local wisdom values ​​of the Lampung region can be included in Indonesian language learning materials in exposition text discussions and can also have implications for the formation of students' character.